2017
DOI: 10.4103/1117-6806.199961
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mandibular condylar changes in patients following orthognathic surgery: A retrospective study

Abstract: Background:Condylar resorption as a cause of relapse after orthognathic surgery is well known. Several authors have presented evidence of the relation between orthognathic surgery and condylar remodeling and resorption. This study was done to appraise the condylar changes along with the form and function following orthognathic surgery, as well as to assess what factors may have contributed to the problems.Methodology:A diagnosis of progressive condylar resorption (PCR) was made by comparison of preoperative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Regarding osteotomies associated with CR. Another interesting finding is that CR was found to be significantly higher postbimaxillary surgery (75.2%).and this was also reported by Hoppenreijs et al 14 and others 16,17,33 . The increased occurrence of CR after BSSO (15.3%) was emphasized by Jose Neto 26 and Jedrzejewski et al 27 where they reported maxilla-mandibular counter-clockwise rotation contributed to influencing TMJ position and health and that TMJ is more favorable to intraoral oblique ramus osteotomy with bimaxillary surgery compared with BSSO with rigid fixation.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Regarding osteotomies associated with CR. Another interesting finding is that CR was found to be significantly higher postbimaxillary surgery (75.2%).and this was also reported by Hoppenreijs et al 14 and others 16,17,33 . The increased occurrence of CR after BSSO (15.3%) was emphasized by Jose Neto 26 and Jedrzejewski et al 27 where they reported maxilla-mandibular counter-clockwise rotation contributed to influencing TMJ position and health and that TMJ is more favorable to intraoral oblique ramus osteotomy with bimaxillary surgery compared with BSSO with rigid fixation.…”
Section: Discussionmentioning
confidence: 56%
“…Another interesting finding is that CR was found to be significantly higher postbimaxillary surgery (75.2%).and this was also reported by Hoppenreijs et al 14 and others. 16,17,33 The increased occurrence of CR after BSSO (15.3%) was emphasized by Jose Neto 26 and Jedrzejewski et al 27 where they reported maxilla-mandibular counter-clockwise rotation contributed to influencing TMJ position and health and that TMJ is more favorable to intraoral oblique ramus osteotomy with bimaxillary surgery compared with BSSO with rigid fixation. According to a survey conducted by de Santanaet al, 2012, 34 the most common OS performed by Oral and Maxillofacial Surgery is BSSO, and the current review revealed that it is the most commonly reported CR complication.…”
Section: Discussionmentioning
confidence: 99%
“…A mistake or overlooked detail during surgical planning, whether in the operating room (condyles) or in the postoperative period (relapse), may require additional surgery. 17,18 From the patients' perspective, the need for reoperation in the postoperative period is one of the most distressing complications. Therefore, meticulous preoperative planning, thorough surgical evaluation, and comprehensive postoperative monitoring are required.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the surgeon should make thorough analysis and planning during the preoperative period. A mistake or overlooked detail during surgical planning, whether in the operating room (condyles) or in the postoperative period (relapse), may require additional surgery 17,18 . From the patients’ perspective, the need for reoperation in the postoperative period is one of the most distressing complications.…”
Section: Discussionmentioning
confidence: 99%